Pengaruh Leverage, Komisaris Independen Dan Ukuran Perusahaan Terhadap Agresivitas Pajak Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Riyansyah, Arief; Putra, Dimas Pratama; Effendi, Rizal (Akuntansi dan Manajemen, 2025)
Tax Aggressiveness is the action of a company in minimizing its tax burden in order to gain more profit. This is detrimental to the state because the source of the state's revenue comes from taxes. Therefore, this study aims to examine the influence of Leverage, Independent Board of Commissioners, and Company Size on Tax Aggressiveness. The population in this study consists of 106 banking companies listed on the Indonesia Stock Exchange (IDX) during the years 2018-2022. The determination of the research sample used the Purposive Sampling method and obtained a sample of 52 Banking Companies based on specific criteria. This study uses the panel data regression analysis technique. Simultaneously, the results of this study indicate that Leverage, the Independent Board of Commissioners, and Company Size have an impact on Tax Aggressiveness. Partially, the results of this study show that Leverage has a positive effect on Tax Aggressiveness, while the Independent Board of Commissioners and Company Size have a negative effect on Tax Aggressiveness.